Evaluation of isolated probiotics on the efficacy of immune system in male and female Wistar rats - Zuhra Bibi; Khadija Ashraf; Areeba Shehzadi; Abdul Rehman; Dilara Abbas Bukhari (Elsevier, 2023)
Probiotics were isolated from fruits and vegetables. Microscopic, biochemical, and molecular tests were carried out for the characterization of strains of probiotics. To assess the effects of isolated probiotics on immunity, male and female (15 + 15) Wistar rats (n = 3) were randomly distributed into 5 groups: 0-day, negative control, positive control (commercially available Lactobacillus acidophilus-14), laboratory isolated probiotics with accession numbers; Lactobacillus plantarum (MZ707748) and Lactobacillus plantarum (MZ729681), respectively. After hematological investigations, the amounts of IgA and IgG in male and female groups were significantly different (p < 0.05). At the same time, the values of Alanine-transaminase (ALT) and Aspartate-aminotransferase (AST) in both genders were average, and there were no differences (p > 0.05). Male probiotic-treated groups had decreased levels of interleukin-6, bilirubin, and creatinine, but female probiotic-treated groups had a slight rise in bilirubin and creatinine values (p = 0.05). Cellular blood count levels of Hematocrit (HCT) and white blood cells (WBC) in male groups showed considerable differences (p < 0.05), while there were no differences (p > 0.05) in female groups. Levels of Red blood cells (RBC) and mean corpuscular hemoglobin concentration (MCHC) showed distinct changes (p < 0.05) in female groups, while these values were insignificant changes (p > 0.05) among male groups. There were considerable differences between the control and groups that were given probiotics. Histopathological results showed no damage to the liver and thymus. A fecal examination of rats was used to examine the viability and survival of Lactobacilli. Based on blood tests, it was observed that the immune system was boosted and improved in probiotic-treated groups compared to control groups.